The Digital Game for the Learning of Reading Skill - Dodi Erwin Prasetyo (Master Program in Linguistics, Diponegoro University, 2022)
The utilization of digital video game was rarely applied for the reading skill. Consequently, there were still no research exploring the integrations of the digital game and the learning of reading skill for long periods, as the jargon of lifelong learning. Therefore, this paper aimed at enriching the perspectives of the integrations of the digital game and a reading skill, at exploring the pedagogical perspectives towards its integrations and at discussing the dilemmas the digital game for teaching and learning a reading skill. This study employed qualitative-interpretative design, while the data were gathered via library research without any participants or respondents. The results highlighted three points. The first point was that the integrations of reading skill through the digital game had to consider the digital game values, the digital game patterns and the reading skill components. The second point was that the pedagogical perspectives had to ponder games’ instructions, teachers’ roles and students’ roles. The third point was dilemmas toward those integrations which were classified as the psychological and pedagogical effects both positively and negatively.